Association Between Body Mass Index and Blood Pressure Among Medical Students of Tertiary Care Teaching Hospital in Birgunj - Shrestha, Esha; Shrestha, Shreesh; Shrestha, Prashanna; Madhikarmi, Nirjala Laxmi (Birat Journal of Health Sciences, 2021)
Introduction: Body mass index is an important parameter associated with a variety of disease processes. The risk of hypertension and cardiovascular diseases increases with an increase in body mass index. The study was conducted to compare the relationship between body mass index and blood pressure. Objective: To evaluate the prevalence and correlate the Obesity and Hypertension in medical students Methodology: The study was conducted in 200 students (113 males and 87 females). Height, weight and blood pressure were recorded from all participants and body mass index was calculated. The recorded body mass index was utilized to divide the student into underweight, normal, over weight and obese category according to the World Health organization body mass index classification. Hypertension was determined from the measure of blood pressure. Then comparison of blood pressure with body mass index was made. Results: Among 200 students 6% were obese, 22% were overweight, 65% were normal and 7% underweight. The mean height was 163cm and mean weight 60.48kg. The mean value of systolic blood pressure (105.85, 115.45, 134.95, 137.16 mmHg) and diastolic blood pressure (70.14, 76.15, 90.72, 93.33 mmHg) increased with increasing body mass index. Conclusion: Overweight and obesity increases the risk of hypertension among students.